2022
DOI: 10.5937/matmor2201027y
|View full text |Cite
|
Sign up to set email alerts
|

Certain integral representations involving hypergeometric functions in two variables

Abstract: Various integral representations of hypergeometric functions have been introduced and investigated due to their important applications in divers fields. In this article, we define some new Euler-type integral representations for the Horn's functions of two variables G1, G2, G3 and H1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Section 2 provides several examples to illustrate this. Some other recent studies related to the function (1) can be found in [14,29,32,35].…”
Section: Introductionmentioning
confidence: 99%
“…Section 2 provides several examples to illustrate this. Some other recent studies related to the function (1) can be found in [14,29,32,35].…”
Section: Introductionmentioning
confidence: 99%